Human-Centered Design, Blockchain, and Decentralized Identity: How can they shape our experience and rights to manage our health: - Hamouda, Hoda (Presenter)
This workshop will introduce students to the use of one blockchain technology in protecting health data. It will engage students in a discussion of the role human-centred design methodology can play in promoting human-centred decision making when it comes to designing what protects individuals’ health data and promote self-sovereign identity. The workshop and discussion will link to, and reflect on some of the themes presented earlier in this series. Hoda Hamouda is the lead user experience designer at the Blockchain@UBC MyPDx Project, in the Institute for Computing, Information and Cognitive Systems (ICICS). Her UI/ UX work revolves around designing tools that let users gain control over their health data, and understand models of self-sovereign identity. Hoda Hamouda is a PhD student, at the Information School at UBC, Department of Archival Studies. Her research focuses on assessing the authenticity of citizen journalism videos from the perspective of archival diplomatics. Hamouda earned her Master’s Degree in Design from Emily Carr University, where she taught for four years. "Human-Centered Design, Blockchain, and Decentralized Identity: How can they shape our experience and rights to manage our health," is a workshop given by Hoda Hamouda on December 9th, 2020, as part of the series "Digital + Creative Knowledge Sharing: Data Management in Creative Research." The series, Digital + Creative Knowledge Sharing: Data Management in Creative Research is supported by Social Sciences and Humanities Research Council of Canada (Research Data Management Capacity Initiative), Emily Carr University Research + Industry Office, VP Academic and Provost Office, Emily Carr Library and First Nations Information Governance Centre.